Two new species and a new record of Bactrocera Macquart (Diptera: Tephritidae: Dacinae: Dacini) from India - David, K. J.; Ramani, S.; Whitmore, Daniel; Ranganath, H. R. (Zootaxa, 2016)
Two new species of Bactrocera Macquart, namely Bactrocera (Calodacus) harrietensis Ramani & David, sp. nov. and Bactrocera (Calodacus) chettalli David & Ranganath, sp. nov., are described from the Andaman and Nicobar Islands and Karnataka, India, respectively. Bactrocera (Zeugodacus) semongokensis Drew & Romig is recorded for the first time from India.